Identification and functional analysis of putative effector proteins from Diaphorina citri and ‘Candidatus Liberibacter asiaticus’ - Dangol, Sarmina; Leite, Márcio Fernandes Alves; Alves, Mônica Neli; Galland, Marc; van Kleeff, Paula J. M.; Kramer, Gertjan; Darolt, Josiane C.; Raiol-Junior, Laudecir L.; Garcia, Rafael Brandão; Peña, Leandro; Wulff, Nelson Arno; de Miranda, Marcelo Pedreira; et al. (Frontiers in Plant Science, 2025)
Phloem feeders, such as the psyllid Diaphorina citri (D. citri), feed on plants by inserting their stylet bundle followed by probing the apoplast before reaching the phloem. The psyllids secrete watery saliva containing various proteins into the phloem, which can act as effectors to facilitate their feeding or modulate host defense responses. Concomitantly, feeding is the main mode of transmitting the Candidatus Liberibacter asiaticus (CLas) bacteria to the phloem. CLas produces several effectors that have been hypothesized to contribute to Huanglongbing (HLB) virulence. Here, we aimed to identify putative effector proteins from both D. citri and CLas. To achieve this, we used different omics techniques on different tissues and organs from both plants and insects. More specifically, we performed transcriptomics on the heads of healthy and CLas-infected D. citri and proteomics of artificial diet and of phloem of four different plant species fed on by healthy and CLas-infected D. citri. Subsequently, we used various criteria and bioinformatics tools to predict putative effectors. This resulted in the identification of four proteins from D. citri [ferritin, prisilkin, CG31997-PA, and pterin-4-alpha-carbinolamine dehydratase-like protein (PCBD)] and two Sec-dependent effectors from CLas, CLIBASIA_04560 and CLIBASIA_05320, that were used for further functional studies. The expression of these six proteins in Nicotiana benthamiana modified the ROS burst triggered by flagellin, indicating that they can indeed function as effector proteins in planta. In addition, expression of the psyllid effectors in planta significantly reduced the growth of Pseudomonas syringae pv. tabaci (Pta).